Graphene Field‐Effect Transistors toward Study of Cardiac Ischemia at Early Stage - Hanna Hlukhova; Dmitry Kireev; Andreas Offenhäusser; Denys Pustovyi; Svetlana Vitusevich (Advanced Electronic Materials)
Abstract Ischemia and reperfusion states are studied in a network of cardiomyocytes as a part of real‐state conditions of heart injuries and inflammations, specifically myocardial infractions. Arrays of graphene field‐effect transistors (GFETs) fabricated in this work are used for extracellular recordings of ischemia states of cardiac cells during the external triggering of the ischemia infarction. The low‐concentrated ischemic buffer solution allows to create a cell‐stress condition resulting in the reperfusion process. The results show that the action potentials recorded with the graphene transistors, especially their shape, and duration of the active segment in measured extracellular action potentials, can be used to characterize the real state of the studied cardiac cell culture. The unique property of GFETs to detect such small changes in the action potential of cells in cardiac healthy and unhealthy states provides prospects for building the next generation of ultrasensitive biosensors, enabling the detection of acute ischemic states at an early stage.